Direct and indirect effects of transformational leadership on volunteers' intention to remain at non-profit organizations - Almas, Shazia, (Colegio Oficial de Psicólogos de Madrid, 2020)
Literature on leadership has provided sufficient evidence that leadership styles increase satisfaction, commitment, and retention of employees. However, there are few studies on the effects of leadership styles on volunteers. This study aims to investigate the possible influence of transformational leadership style on retention of volunteers. Our first hypothesis is that if a volunteer coordinator has a transformational leadership style, there is a higher intention to remain. Our second hypothesis is that this relationship is mediated by the variables of the three-stage model of volunteers duration of service (satisfaction, organizational commitment, and role identity). To test these hypotheses, a sample of 417 volunteers (73% women), from 17 non-profit organizations, with an average age of 44 years, was surveyed. Joint results of a multiple regression analysis and path analysis supported the proposed model (CFI, GFI and NFI = .99, RMSEA < .06). Results indicate that when volunteer coordinators have a transformational style, volunteers have a higher intention to remain and that this relationship between transformational leadership style and intention to remain is partially mediated by satisfaction, organizational commitment, and role identity. The results seem to indicate that a useful strategy when running programs to increase the retention of volunteers is to train their coordinators in transformational leadership skills.